ChemInform Abstract: A New Cyclopropyl‐Triterpenoid from Ochradenus arabicus. Issue 3 (29th December 2015) - Ali, Liaqat; Ahmad, Riaz; Ur Rehman, Najeeb; Latif Khan, Abdul; Hassan, Zahid; Shamim Rizvi, Tania; Al‐Harrasi, Ahmed; Khan Shinwari, Zabta; Hussain, Javid
Abstract: The new cyclopropyl‐triterpenoid is isolated along with four known compounds from the aerial parts of Ochradenus arabicus.